ENHANCING FINANCIAL TRANSPARENCY IN INDONESIAN REGIONAL GOVERNMENT: A VARIANCE ANALYSIS APPROACH (Evidence From Government of Enrekang Regency, South Sulawesi Province - Indonesia) - Hasanuddin, Hasanuddin; Sahrullah, Sahrullah; Khaliq, Abdul (Jurnal Ilmiah Ekonomi Dan Bisnis, 2023)
Purpose: Although the strangulation related to regional autonomy has long been rolling and applied by all regions of the provincial capital that existed in Indonesia, it still leaves various issues, especially regarding performance achieved through financial management. This study aims to analyze and look at the achievement of financial performance accountability concerning using expenditure income budgets. Method: The analysis method used is an analysis of variance and growth through two significant stages of the investigation, each through two testing processes. The data used is time-series data about the realization of using the expenditure budget in the 2016-2020 period. Findings: The results show an income budget of 93.64%, a 90.95% expenditure budget, a revenue budget growth of 3.78%, and a spending growth of 4.49%. Although statistically, the use of the budget and the revenue and expenditure growth rate has increased on the revenue usage side, it could have been more efficient and proven to be a high percentage of income used in financing district government spending. The government should have undertaken and implemented strategies to adjust for the use of the budget. Novelty: Some research related to the issue of transparency of financial statements through this approach has been carried out previously, but the differences are present at the time of the study. The limitation of this study is not to analyze the ratio needed and not to analyze the period cut off in the current budget period and for researchers conducting similar research to meet research limitations and expand sampling.